Assessing Intertemporal Socioeconomic Inequalities in Alcohol Consumption in South Africa - Fontes Marx, Mayara; London, Leslie; Harker, Nadine; Ataguba, John E. (Frontiers in Public Health, 2021)
Background: This paper assesses changes in the socioeconomic inequality in alcohol consumption by exploring whether alcohol consumption (current and binge drinkers) is more prevalent among the wealthier (pro-rich) or poorer (pro-poor) group over time. Methods: Data come from the 2008, 2010/11, 2012, and 2014/15 waves of the National Income Dynamics Study (NIDS). Various equity stratifiers (sex, age, race, and rural/urban) are used to analyze the prevalence of alcohol consumption and to investigate differences in socioeconomic inequalities. Changes in socioeconomic inequality in alcohol consumption between 2008 and 2014/15 were also assessed using the concentration index. Results: Current drinkers were more concentrated among richer South Africans, while binge drinkers were concentrated among the poorer population. For current drinkers, irrespective of sex, race, age, and urban, socioeconomic inequality in alcohol consumption had become less pro-rich between 2008 and 2014/15; while inequality in binge drinking, outside of the Asian/Indian and rural categories, had become less pro-poor between 2008 and 2014/15. Conclusion: The results show evidence that binge drinking is a bigger problem among those of low-SES, young individuals, male and African populations. This paper concludes that the SA government should continue to push forward policies aiming to reduce the prevalence of binge drinking.